Hubungan Pengetahuan Ibu Dengan Pemakaian Alat Kontrasepsi Suntik 1 Bulan di Puskesmas Lahusa Nias Selatan Tahun 2023 - Kaniawati Hulu; Adelina Sembiring; Lisbet Gurning (Lembaga Pengembangan Kinerja Dosen, 2024)
Population growth in Indonesia continues to increase every year. If the rate of population growth in Indonesia is currently stagnant. It is estimated that Indonesia's population will double every 5 years. The increase in population has an impact on issues of food security, meeting energy needs, environmental control, and the low level of Indonesia's Human Development Index (HDI). Meanwhile, in the health sector, the increase in population also has an impact on the high Maternal Mortality Rate (MMR). The aim of the research was to determine the relationship between maternal knowledge and the use of injectable contraceptives for 1 month at the Lahusa South Nias Community Health Center in 2023.The type of research carried out was Descriptive Analytical with a cross sectional approach, the sample in the study was 43 people using a Random Sampling System. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi square The results of the cross-tabulation research showed that the majority of mothers' knowledge was good in using contraceptives as many as 12 people (92.3%) with Chi-Square showing a p value of 0.000. So Ho is rejected and Ha is accepted, which means there is a relationship between the mother's knowledge and the use of injectable contraceptives for 1 month at the Lahusa Health Center, South Nias in 2023. The conclusion is that it is hoped that providing a 1-month injectable contraceptive will make it easier and reduce the costs of carrying out contraception at the Lahusa South Nias Community Health Center in 2023.